2019
DOI: 10.1002/hbm.24557
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical correlates of food addiction symptoms and body mass index in the general population

Abstract: The food addiction model suggests neurobiological similarities between substance‐related and addictive disorders and obesity. While structural brain differences have been consistently reported in these conditions, little is known about the neuroanatomical correlates of food addiction. We therefore aimed to determine whether symptoms of food addiction related to body mass index (BMI), personality, and brain structure in a large population‐based sample. Participants of the LIFE‐Adult study (n = 625; 20–59 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 60 publications
5
26
1
Order By: Relevance
“…Our results showed a positive relation between FA and BMI, which is consistent with other research [ 4 , 34 , 36 , 37 ]. Individuals who were overweight or with obesity had a higher relative risk of FA than those who were normal or underweight according to either BMI or body fat percentage measurement [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed a positive relation between FA and BMI, which is consistent with other research [ 4 , 34 , 36 , 37 ]. Individuals who were overweight or with obesity had a higher relative risk of FA than those who were normal or underweight according to either BMI or body fat percentage measurement [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study aiming to characterizing FA as a phenotypical construct in patients with different types of EDs and obesity via a factor analysis, results suggested that patients with FA and BN presented with more severe ED psychopathology [ 32 ]. Moreover, other work suggested that, among women with a high BMI, the presence of a relationships between early life adversities and FA may be underpinned by specificities in brain regions implicated in reward and emotional regulation [ 33 , 34 , 35 ]. Similarly, patients with PTSD were described to be at higher risk for FA and EDs due to the potential mediating role of emotional dysregulation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, greater adiposity for age was related to increased thickness of the left fusiform cortex, extending to the lateral occipital lobe, and right lateral occipital cortex. Visceral fat mass has been positively related to bilateral occipital thickness in obese adolescents (Saute et al, 2016), and high BMI has been negatively associated with lateral occipital cortex thickness in several adult cohorts (Beyer et al, 2019; Medic et al, 2016). These findings broadly align with theories of altered visuospatial processing in obesity, where external cues are thought to override interoceptive signals (Schachter, 1968).…”
Section: Discussionmentioning
confidence: 99%